Influence of Alkaline Activators on Unconfined Compressive Strength of Saline Soils Stabilised with Ground Granulated Blast Furnace Slags - Guoqi Xing; Lijun Zhang; Wei Xuan; Yueyue Pan; Yue Zhao; Bing Zhang (Advances in Civil Engineering)
To mitigate the environmental impact induced by CO2 emissions and nonrenewable resource consumption, which are typically associated with Portland cement production, ground granulated blast furnace slags (GGBSs) are usually added to the cement. In this study, the stabilisation effect of alkali-activated GGBS on saline soil and the hydration products of alkali-activated GGBS were investigated by unconfined compressive strength tests and scanning electron microscopy, respectively. The results show that Ca(OH)2 and NaOH as alkaline activators for GGBS significantly improve the unconfined compressive strength of saline soils. This strength is also enhanced by Na2SO4; however, the increase is considerably less than that provided by Ca(OH)2 and NaOH. In contrast, Na2CO3 is not a suitable alkaline activator for GGBS and has no significant effect on the unconfined compressive strength of saline soils. The study results further show that the morphology of hydration products varies because of the different alkaline activators involved in the hydration reaction with GGBS in saline soils.